(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
This paper analyses whether remittances affect household consumption expenditure in Kyrgyzstan using Life in Kyrgyzstan Survey datasets collected during 2010-2016. We employ a measure of remittance as families who received remittance for the past 12 months and consumption is measured as both food and non-food expenditure separately. A remittance gravity model is estimated using panel data and a Two Stage Least Squares method was employed to tackle double endogeneity issue. We conclude that foreign remittances have an important role in making consumption decisions for Kyrgyz households. Moreover, this study supports the permanent income theory, which states that families accept remittances as permanent income and do not consider sources of income while making food and non-food expenditure decisions. Therefore, we provide evidence from Kyrgyzstan with policies intended to support remittance inflows which can in turn improve household consumption.